Pengalaman Orangtua Selama Anak Dirawat dengan Penyakit Akut dan Kritis: Literature Review - Yayah; Wanda, Dessie (Dunia Keperawatan: Jurnal Keperawatan dan Kesehatan, 2021)
Acute and critical illness threats can cause death. Having an acute and critically ill child who is admissionprovides unique experiences for parents. The aim to describe the experiences during which children undergotreatment for acute and critical illnesses. Methods with online data-based searches ScienceDirect, PubMed,and Wiley published in 2016-2020. The keywords used were mother OR parent AND child AND "acuteillness" AND hospitalization OR inpatient care. The results of the analysis of the themes: world and foreignenvironment; problems controlling the parent; negative emotions;characteristic of parent contribute; needfor health service facilities; and care needs for parents. Conclusion: parents experience a psychologicalresponse that requires attention and intervention from health workers that they are able to adapt to thesituation they feel. It is important to apply the FCC concept with appropriate strategies in nursing care forchildren during child in acute and critical care setting.